Problems and coping strategies of organizational members with dual role position as employee-shareholder in a publishing company in Indonesia - Annur, Saraswati Desch (2012)
This qualitative case study examined problems, contributing factors to the problems, and coping strategies associated with the dual role position as employee-shareholder at PT. Griya Asri Prima, an Indonesian company specialized in magazine publication. The dual role position was a response to a financial crisis and government regulations faced by the organization. The specific objectives of the study were (i) to identify problems encountered by organizational members as a result of assuming the dual role position as employee-shareholder, (ii) to identify factors that contribute to the problems of dual role position, and (iii) to identify coping strategies adopted by the members in dealing with their dual role problems. Fifteen semi structured, one-on-one interviews were conducted which provided the data to answer the research questions and objectives. This study concluded that the dual role situation as employee and shareholder is a problematic in nature. The problems experienced by the members of PT. Griya Asri Prima associated with the dual role position are: rigid in accepting dual roles, miscommunication, abuse of power, incapable to differentiate roles, unable to act as shareholder, stress, and conflict of interest. Meanwhile, there are three contributing factors to the problems: generation gap between senior and junior employees, human factors, and psychological factor. There are two coping strategies used by the members: problem focused coping (active coping, suppression of competing activities, restrain coping, and seeking social support for instrumental reason) and emotion focused coping (denial and turning to religion). The suggestions from this research are to (i) establish individual and group capacity training to enhance competency in actualizing dual role throughout employees daily work, (ii) involve employees at all levels in determining organizational policies, (iii) introduce organization bulletin or information board to inform employees about organizational issues, (iv) conducting frequent discussion between the management and employees, and (v) hire employees according to their appropriate skill levels and replace incompetent employees.